Reformasi Sistem Rekrutmen Hakim Konstitusi Indonesia yang Sejalan dengan Nilai Kerakyatan Pancasila - Hamadi, Ibrahim Ghifar; Angelina, Feymi (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2024)
Abstract: As a constitutional state grounded in Pancasila, Indonesia requires a transparent, objective, and accountable system for recruiting constitutional judges to safeguard judicial independence. Unfortunately, the current mechanism is fraught with conflicts of interest and lacks meaningful public participation. There are discrepancies in recruitment standards among the proposing institutions, resulting in inconsistencies in the quality of constitutional judges. Non-transparent and unaccountable mechanisms hinder the attainment of judicial integrity and professionalism. This research aims to analyze and formulate an ideal reform for the recruitment system of constitutional judges based on Pancasila values and meaningful public involvement. This study employs a doctrinal legal research method. Data collection was conducted through library research, consisting of primary and secondary legal materials. The findings reveal that the weaknesses in the current mechanism can be addressed through two main innovations: the establishment of an independent selection panel and the SHAKTI platform (Transparent and Informative Selection of Constitutional Judges). These mechanisms ensure not only transparency and public participation but also promote the independence and integrity of constitutional judges.Keywords: Constitutional Judges, Recruitment, Pancasila. Abstrak: Sebagai negara hukum yang berlandaskan Pancasila, Indonesia memerlukan sistem rekrutmen hakim konstitusi yang transparan, objektif, dan akuntabel untuk menjaga kemerdekaan kekuasaan kehakiman. Sayangnya, mekanisme yang ada saat ini masih dipenuhi konflik kepentingan dan kurang melibatkan partisipasi publik yang bermakna. Terdapat perbedaan standar rekrutmen antar lembaga pengusul yang menyebabkan ketidakseragaman kualitas hakim konstitusi. Mekanisme yang tidak transparan dan akuntabel menjadi penghalang tercapainya integritas dan profesionalisme hakim. Penelitian ini bertujuan mengkaji dan merumuskan reformasi sistem rekrutmen hakim konstitusi yang ideal, berbasis nilai-nilai Pancasila, serta melibatkan publik secara bermakna. Penelitian ini menggunakan metode penelitian hukum doktrinal Pengumpulan data dilakukan melalui studi kepustakaan berupa bahan hukum primer dan bahan hukum sekunder. Hasil penelitian menunjukkan bahwa kelemahan mekanisme saat ini dapat diatasi dengan dua inovasi utama, yaitu pembentukan lembaga panel seleksi yang independen dan situs SHAKTI (Seleksi Hakim Konstitusi Transparan dan Informatif). Mekanisme ini tidak hanya menjamin transparansi dan partisipasi publik tetapi juga mendorong independensi serta integritas hakim konstitusi.Kata kunci: Hakim Konstitusi, Rekrutmen, Pancasila.